2023
DOI: 10.3389/fpubh.2023.1110216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and influencing factors of chronic pain in middle-aged and older adults in China: results of a nationally representative survey

Abstract: BackgroundWith China's rapidly aging population, chronic pain has become a major public health issue. This article aims at determining associations between chronic pain and multiple factors, including demographic characteristics, health status, and health service utilization of middle-aged and older adults in China.MethodsWe selected all the 19,829 respondents who were over 45 years old from the China Health and Aging Tracking Survey 2018 (CHARLS) as our study population. The key information in terms of the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Studies have shown a two-way connection between back pain and serious depression in US adults, indicating a shared neuroplasticity process that underlies their link [46]. A combined analysis of two national aging cohort studies has further supported the connection between pain and symptoms of depression, indicating that individuals with pain are at a higher risk of developing depressive symptoms and vice versa [47,48]. These studies provide vital insights into the complicated link between chronic pain and neuroplasticity, highlighting the interaction between persistent pain conditions and the brain's adaptive modifications.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown a two-way connection between back pain and serious depression in US adults, indicating a shared neuroplasticity process that underlies their link [46]. A combined analysis of two national aging cohort studies has further supported the connection between pain and symptoms of depression, indicating that individuals with pain are at a higher risk of developing depressive symptoms and vice versa [47,48]. These studies provide vital insights into the complicated link between chronic pain and neuroplasticity, highlighting the interaction between persistent pain conditions and the brain's adaptive modifications.…”
Section: Discussionmentioning
confidence: 95%
“…A variety of age groups, including adolescents and elderly people, suffer from pain. A recent large-scale national cross-sectional study [63] showed that 60.02% of middle-aged and elderly people in China had experienced body pain. Another study, which included data from 42 countries and territories, showed that 23.6% of adolescents reported experiencing localized specific single-site pain.…”
Section: Discussionmentioning
confidence: 99%
“…This study also has some limitations; information on the prevalence of chronic diseases and ADL impairment was obtained by self-report, which may be subject to recall bias. However, the present study was able to reduce recall bias to a greater extent by using a scientific and well-recognized scale to measure ADL impairment in middle-aged and older adults and by using self-reported illnesses diagnosed by healthcare institutions as the study factor ( 14 ). Therefore, the likelihood of recall bias is small, and the results have a certain degree of reliability.…”
Section: Discussionmentioning
confidence: 99%
“…The product of the basic and adjusted weights was used to obtain a combined weight for each individual to represent the probability of its true occurrence in the aggregate. To make the data a better representation, the weighting considers a number of factors, including the sampling design, missingness, non-response rate, non-coverage, geographical location, gender, age, and socioeconomic characteristics ( 14 ). The ethical approval for the CHARLS project was received from the Ethics Review Committee of Peking University, and informed consent was obtained from all participants during the data collection.…”
Section: Methodsmentioning
confidence: 99%